Development of a novel affinity chromatography resin for platform purification of lambda fabs. (6th August 2014) - Eifler, Nora; Medaglia, Giovanni; Anderka, Oliver; Laurin, Linus; Hermans, Pim
<x xml:space="preserve">Abstract</x> Antigen‐binding fragments (Fabs) are novel formats in the growing pipeline of biotherapeutics. Sharing similar features to monoclonal antibodies (mAbs) with regard to expression, Fabs are considered as unchallenging for upstream development. Yet for downstream processing, the mature mAb downstream purification platform is not directly applicable. New approaches need to be found to achieve a lean purification process that maintains quality, productivity, and timelines while being generically applicable independent of the expression system. In a successful collaboration, BAC BV, GE Healthcare, and Novartis Pharma AG have developed a new affinity chromatography medium (resin) suitable to support cGMP manufacturing of lambda Fabs. We show that using this novel chromatography medium for the capture step, a purification platform for lambda Fabs can be established. © 2014 American Institute of Chemical Engineers Biotechnol. Prog., 30:1311–1318, 2014